Acoustic emission monitoring of fiber reinforced bridge panels - Flannigan, James Christopher (Kansas State University, 2008)
Two fiber reinforced polymer (FRP) bridge deck specimens were analyzed by means of acoustic emission (AE) monitoring during a series of loading cycles performed at various locations on the composite sandwich panels' surfaces. These panels were subjected to loads that were intended to test their structural response and characteristics without exposing them to a failure scenario. This allowed the sensors to record multiple data sets without fear of having to be placed on multiple panels that could have various characteristics that alter the signals recorded. The objective throughout the analysis ias to determine how the acoustic signals respond to loading cycles and various events can affect the acoustical data. In the process of performing this examination several steps were taken including threshold application, data collection, and sensor location analysis. The thresholds are important for lowering the size of the files containing the data, while keeping important information that could determine structurally significant information. Equally important is figuring out where and how the sensors should be placed on the panels in the first place in relation to other sensors, panel features and supporting beams. The data was subjected to analysis involving the response to applied loads, joint effects and failure analysis. Using previously developed techniques the information gathered was also analyzed in terms of what type of failure could be occurring within the structure itself. This somewhat aided in the analysis after an unplanned failure event occurred to determine what cause or causes might have lead to the occurrence. The basic analyses were separated into four sets, starting with the basic analysis to determine basic correlations to the loads applied. This was followed by joint and sensor location analyses, both of which took place using a two panel setup. The last set was created upon matrix failure of the panel and the subsequent investigation.
Keywords: Fiber Reinforced Polymer; Acoustic Emission; Bridge Deck; Data Analysis; Engineering, Civil (0543); Engineering, Mechanical (0548)